DOP49 Effectiveness and safety of vedolizumab in a matched cohort of elderly and young Inflammatory Bowel Disease patients - LIVE Study-Group. (27th May 2021) - Pugliese, D; Privitera, G; Armuzzi, A
Abstract: Background: Vedolizumab is the first biologic tested for the treatment of elderly patients with moderate-to-severely active ulcerative colitis (UC) and Crohn's disease (CD) in the GEMINI program. However, little real-life data have been reported on its use in the elderly population. In this work, we present data on vedolizumab effectiveness and safety in a large cohort of elderly UC and CD patients matched to younger patients. Methods: The Long-term Italian Vedolizumab Effectiveness (LIVE) study included CD and UC patients started on vedolizumab from April 2016 to June 2017 at 47 centers of the Italian Group for the study of Inflammatory Bowel Disease (IG-IBD). Elderly (E-) patients (≥ 65-year-old) were included for this analysis and matched 1:2 to younger (Y-) patients; patients were then prospectively followed-up until June 2019. Primary endpoints were vedolizumab persistence and safety. Results: Of 1111 patients, 198 E-patients (mean age 71 ± 5 years; 108 UC, 90 CD) were included in the analysis and matched with 396 Y-patients (45 ±12 years; 205 UC, 191 CD). After matching, the 2 cohorts were overall comparable, but patients in the Y-group were significantly more likely to have perianal disease, previous exposure to immunosuppressants, and to anti-TNF-α and less likely to be on concomitant steroids at baseline. For UC, persistence in the E- and Y-groups were 69.9% vs and 81.4% at 12 months, and 51.4% vs 67.6% at 24 months (p<0.05 for both). Significant differences were also observed in terms of steroid-free clinical remission (SFCR) (31.5% vs 42.9%, 32.4% vs 42.9% at 12 and 24 months, p<0.05 for both) and biochemical remission (22.2% vs 38%, 25.9% vs 40.5% at 12 and 24 months, p<0.05 for both). Endoscopic remission was observed in 17/75 (22.7%) E-patients and 50/141 (35.5%) Y-patients (p=0.05). For CD, persistence was 75.6% vs 75.1% at 12 months, 52.4% vs 59.4% at 24 months, for the E- and Y- group respectively (p=ns for both). Similarly, rates of SFCR were comparable between the 2 cohorts. Notably, a significantly higher rate of biochemical remission was observed in the Y-group at 24 months (21.1% vs 30.9%, p<0.05). Endoscopic remission was observed in 13/48 (27.1%) E-patients and 25/98 (28.1%) Y-patients (p=ns). A total of 51 and 94 adverse events (AEs) were observed in the E-group and Y-group, respectively: the rate of AEs was comparable between the 2 groups (p=ns). Of note, E-patients had a higher likelihood of suspending vedolizumab due to AEs (p<0.05). Conclusion: The data show that vedolizumab can be considered a safe option in elderly patients; however, its efficacy in elderly UC patients (in terms of persistence, SFCR and biochemical remission) seems to be reduced compared to younger UC patients, while no difference was observed in CD.